STUDY ON STRENGTH CONSTRAINTS OF OPTIMIZATION OF GEARBOX BASED ON FATIGUE THEORY - ZHANG XinYuan; DING XiaoHong (Jixie qiangdu)
In view of the fact that the gearbox body has excess strength and the mass is too heavy,it needs to be optimized.In the current research on optimization constraints,most scholars use static strength as the strength constraint but lack the consideration of fatigue strength. Therefore,based on the fatigue theory,combined with the rain flow cycle count,according to the transmission box specifications to linearly extrapolate the number of cycles to obtain the number of cycles and then as its life,compare the number of extrapolation cycles with the number of test load spectrum cycles,combined with S-N curve of 90%reliability,to obtain the theoretical stress amplitude. According to the dynamic load coefficient,the maximum stress is calculated.Compare it with tensile strength to get individual component strength constraints. It can provide more accurate constraints for optimization,save the subsequent verification process,and improve the optimization efficiency.